TO THE DIFFERENTIAL DIAGNOSIS OF MULTISYSTEM INFLAMMATORY SYNDROME IN CHILDREN ASSOCIATED WITH A NEW CORONAVIRUS INFECTION - Котович, Марина Михайловна; Яковлев, Яков Яковлевич; Сергиенко, Григорий Михайлович; Матвеева, Наталья Владимировна; Требунских, Александр Иванович; Гельд, Юлия Германовна (Mother and Baby in Kuzbass, 2022)
Pediatric inflammatory multisystem syndrome (MIS-C), or «pediatric multisystem inflammatory syndrome temporarily associated with SARS-COV-2 (PMIS-PT)» is a rare, severe complication or manifestation of new coronavirus infection. Clinical and laboratory symptoms of this disease (fever, rash, myocarditis, abdominal pain and other gastrointestinal symptoms; increased levels of CRP, procalcitonin, D-dimer, troponin and others) may be found in Kawasaki syndrome, severe bacterial infections, collagenosis, vasculitis. Despite the existing criteria, there may be doubts in establishing the diagnosis. This article presents clinical observations demonstrating certain difficulties in the differential diagnosis of MIS-C.